THE METHOD OF SOFTWARE RELIABILITY EVALUATION AND PREDICTION BASED ON THE MODEL WITH DYNAMIC INDEX OF PROJECT SIZE - Seniv, Maksym; Yakovyna, Vitaliy; Chabanyuk, Yaroslav; Fedasyuk, Dmytro (International Journal of Computing, 2011)
The software reliability evaluation and prediction method based on the model with dynamic index of project size is examined in this article. The support decision making procedure during software production which is based on the adequacy criterion of software testing is developed. The example of developed method based on testing data of industrial software product is proposed.